Fault location identification in power transmission networks: using novel nonintrusive fault-monitoring systems - Chang, Hsueh-Hsien; Yang, Chuan Choong; Lee, Wei-Jen (IEEE, 2021)
This article proposes a novel fault-localization method that is based on the nonintrusive fault-monitoring (NIFM) techniques in high-voltage/extra-high-voltage (HV/EHV) power transmission networks. In this work, the fault signals measured at the utilities are extracted by the hyperbolic S-transform (HST) before going through the identification process. To carefully select coefficients of the HST representing fault transient signals and reduce the size of inputs for recognition algorithms, power-spectrum-based HST is adopted in this article to quantitatively transform the HST coefficients (HSTCs). After the processes of feature selection, the fault-location indicator is recognized by the support vector machines (SVMs). To examine and validate the proposed methodology, various fault types in a sample power system are simulated by using the electromagnetic transient program (EMTP). The simulation results reveal that the proposed methods demonstrate a high success rate of fault-location identification in power transmission networks for NIFM applications.